The role of antioxidants in prevention of male infertility - N. P. Naumov; P. A. Scheplev; V. V. Polozov (Андрология и генитальная хирургия, 2019)
The study objective is to discuss the most studied antioxidants, using for the enhancement of human reproductive characteristics, and to describe their mechanisms of action, effects and recommended doses.Results. Oxidative stress remains a key factor that can affect the reproductive outcome, either naturally or with assisted reproductive technology. Zinc, selenium, folic acid, vitamin E, vitamin C, carnitines, N-acetyl-L-cysteine, coenzyme Qw, lycopene most commonly used for mono- or combination therapy.Conclusion. The identification and treatment of oxidative stress by reducing reactive oxygen species (antioxidant therapy) seems an attractive tactic in the prevention and treatment of infertility.